Effects of Green Transformational and Ethical Leadership on Green Creativity, Eco-Innovation and Energy Efficiency in Higher Education Sector of Indonesia - Bahzar, Moh. (International Journal of Energy Economics and Policy, 2019)
The role of energy efficiency is regarded as the prime goal for reducing environmental pressures; co-existing in the form of the organization's extensive energy dependence and resource depletion. Therefore, the current examination proposed to test the empirical association of ETL and TRL in influencing green creativity (GRC) and eco-innovation (ECI) in higher educational institutes of Indonesia. Moreover, given the significance of energy efficiency in curtailing negative effects of power consumption in environmental degradation, the present study also examined the impact of GRC and ECI on energy efficiency (ENE) by particularly focusing higher educational institutes. The study applied PLS-SEM, and the results recommended that eco-innovation and have a positive and significantly influenced by green transformational leadership. Moreover, the results further suggested that eco-innovation and green capacity have significantly and positively impacted by ethical leadership. Finally, the results of PLS-SEM confirm that eco-innovation and green capacity have significantly and positively impact on energy efficiency on international schools in Indonesia. In summary, the results confirmed that green transformational leadership, eco-innovation and green creativity are very important and significant contributor in enhancing energy efficiency in higher education sector of Indonesia. The study recommended that government need to pay more attention on environmental friendly innovations to reduce environmental issues and enhance energy efficiency in Indonesia. Keywords: Green transformational leadership, ethical leadership, energy efficiency, Indonesia. JEL Classifications: L8, O3 DOI: https://doi.org/10.32479/ijeep.8372